Решите уравнение: (5a - 9) *a=a * (8a - 3)

Решите уравнение: (5a - 9) *a=a * (8a - 3)
Гость
Ответ(ы) на вопрос:
Гость
1) (5а-9)*а = а*(8а-3)                                                                                   5а-9=8а-3                                                                                                           3-9=8а-5а                                                                                                    -6=3а                                                                                                                   а=(-6):3                                                                                                               а=-2.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы